The Nociceptin/Orphanin FQ Receptor Antagonist J-113397 and l-DOPA Additively Attenuate Experimental Parkinsonism through Overinhibition of the Nigrothalamic Pathway - Marti, Matteo (J Neurosci, 2007)
By using a battery of behavioral tests, we showed that nociceptin/orphanin FQ receptor (NOP receptor) antagonists attenuated parkinsonian-like symptoms in 6-hydroxydopamine hemilesioned rats (Marti et al., 2005). We now present evidence that coadministration of the NOP receptor antagonist 1-[(3R,4R)-1-cyclooctylmethyl-3-hydroxymethyl-4-piperidyl]-3-ethyl-1,3-dihydro-2H benzimidazol-2-one (J-113397) and l-DOPA to 6-hydroxydopamine hemilesioned rats produced an additive attenuation of parkinsonism. To investigate the neurobiological substrates underlying this interaction, in vivo microdialysis was used in combination with behavioral measurements (bar test). J-113397 and l-DOPA alone reduced the time on bars (i.e., attenuated akinesia) and elevated GABA release selectively in the lesioned substantia nigra reticulata. J-113397 also reduced nigral glutamate levels, whereas l-DOPA was ineffective. J-113397 and l-DOPA coadministration produced additive antiakinetic effect, which was associated with additive increase in nigral GABA release but no additional reductions in glutamate levels. To investigate whether the increase in nigral GABA release could translate to changes in nigrothalamic transmission, GABA release was monitored in the ventromedial thalamus (one of the main target areas of the nigrothalamic projections). J-113397 and l-DOPA decreased thalamic GABA release and attenuated akinesia, their combination resulting in a more profound effect. These actions were prevented by perfusing the voltage-dependent Na(+) channel blocker tetrodotoxin or the GABA(A) receptor antagonist bicuculline in the substantia nigra reticulata. These data demonstrate that J-113397 and l-DOPA exert their antiparkinsonian action through overinhibition of nigrothalamic transmission and suggest that NOP receptor antagonists may be useful as an adjunct to l-DOPA therapy for Parkinson's disease.